2020
DOI: 10.1002/suco.202000038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fibers on the temperature field and radial deformation behavior of self‐compacting concrete pipes under cyclic fire condition

Abstract: In this paper, the radial deformation of fiber reinforced self‐compacting concrete (SCC) pipes under cyclic fire conditions is studied. A series of experimental study on the temperature fields and radial deformation properties of steel mesh, polypropylene fiber (PP fiber), and macro steel fiber (SF) reinforced SCC pipes subjected to fire is carried out. A novel method for measuring the deformation of pipes under high temperature has been proposed. The results indicate that both micro PP fiber and macro SF are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(30 reference statements)
1
0
0
Order By: Relevance
“…However, the internal temperature of the specimen continued to rise when the water inside was completely evaporated. Liu et al [ 57 ] and others have also confirmed this.…”
Section: Resultssupporting
confidence: 56%
“…However, the internal temperature of the specimen continued to rise when the water inside was completely evaporated. Liu et al [ 57 ] and others have also confirmed this.…”
Section: Resultssupporting
confidence: 56%